The Serial and the Book in Nineteenth-Century Britain: Intersections, Extensions, Transformations - Brake, Laurel (Mémoires du livre / Studies in Book Culture)

(untitled) (Groupe de recherches et d’études sur le livre au Québec, 2017)
In the nineteenth-century book trade in the UK, the proliferation of the book as a cheap reading format developed at the same time as an increase in literacy, the popularity of fiction and the novel, the rise of circulating libraries, and an explosion of the press, especially the repeal of taxes between 1855-1861 on newspaper sheets, advertisements, and paper. These many factors combined to foster a significant interdependence between the serial and the book. This article notes the variety of serial forms in the period: magazine instalments; part-issue; three-volume novels; and book series or “Libraries” of cheap reprints, and it explores differences among book editions. It examines the constant traffic created by this interdependence including remediation between periodical articles and fiction in periodicals and books, largely from periodical to book, but also in the opposite direction, as periodicals routinely printed reviews of books, often with long extracts. It argues that renowned British authors, scientists and historians were journalists, and shows how their work is routinely found in popular as well as literary discourses. “Authors” were also editors and sometimes proprietors of journals, while book publishers created house magazines to lure authors to contracts with initial remuneration, followed by book publication. The piece will also discuss how publication of longer works in successive instalments affects the form of the novel or non-fiction narrative.